Placenta percreta with silent rupture of the uterus - Passini Junior, Renato; Knobel, Roxana; Barini, Ricardo; Marussi, Emílio (São Paulo Medical Journal, 1996)
We report a case of placenta percreta diagnosed by ultrasound and color doppler image at the fourteenth week of gestation. Initial approach was a trial of IM methotrexate followed by total hysterectomy, during which was observed a rupture of the uterus with the adherence of the placenta to the posterior region of the bladder. We also present a literature review on the incidence of placenta percreta, etiology, diagnosis, treatment, and complications.